Financial Constraints and Girls' Secondary Education: Evidence from School Fee Elimination in The Gambia - Moussa P. Blimpo; Ousman Gajigo; Todd Pugatch (Institute for the Study of Labor (IZA), 2015)
We assess the impact of large-scale fee elimination for secondary school girls in The Gambia on the quantity, composition, and achievement of students. The gradual rollout of the program across geographic regions provides identifying variation in the policy. The program increased access to secondary education substantially without harming learning outcomes. We find an increase of around 50% in the number of girls and boys taking the high school exit exam from a low baseline, as well as a 0.1 standard deviations gain in test scores in response to the program. This result is notable in a setting where expanded access could put additional strains on limited resources and the quality of schools. These findings suggest that financial constraints remain serious barriers to post-primary education and that efforts to expand access to secondary education need not come at the expense of learning in low-income countries like The Gambia.
Keywords: O15; I21; C93; 330; secondary school; school fee elimination; gender gap; Gambia